The ability of potassium-solubilizing fungi isolated from leucite potassium rock deposits (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Anwar AR, Ala A, Kuswinanti T, Syam’un E. 2022. The ability of potassium-solubilizing fungi isolated from leucite potassium rock deposits. Biodiversitas 23: 6579-6586. Present investigation was aimed to explore the potassium-dissolving ability of some indigenous fungi living in Indonesian leucite tuffs from volcanic rock members of Camba Formation in Barru Regency, South Sulawesi Province. There are no such findings on potassium-solubilizing fungi from South Sulawesi Province. The recent study isolated some fungi strains from the rhizosphere of vegetation found in the potassium rock deposits using Alexandrov media. A total of 22 fungal strains were isolated and tested for their ability to dissolve potassium bound to the potassium carrier minerals, qualitatively and quantitatively. Production of indole-3-acetic acid (IAA) and gibberellic acid (GA3) were also measured to test the ability of the fungus to produce growth regulator compounds. Fungal isolates with the highest dissolution index (IP) values were MgT1Pb, RgGc, PT3Pe, PT3Pa, JbT2Pa, JbT2Pd, and JbT2Pp. The highest amount of exchangeable potassium (K-exch.) was JbT2Pa with the amount of 919.8 ppm and MgT1Pb of 69.33 ppm. The isolate capable of producing the highest IAA was PsT2Pe at 6.820 ppm while the RgGd isolates resulted in the highest production of GA3 hormone at 4.116 ppm.
Keywords: Gibberellic acid, indole acetic acid, insoluble K, potassium-solubilizing fungi, rock deposits, solubilization